Impact of guidelines and enhanced antibiotic stewardship on reducing broad-spectrum antibiotic usage and its effect on incidence of Clostridium difficile infection - Talpaert, M; Rao, G; Cooper, B; Wade, P (2011)
Objectives: To evaluate the impact of an 'intervention' consisting of revised antibiotic guidelines for empirical treatment of common infections and enhanced stewardship on reducing broad-spectrum antibiotic usage and its effect on incidence of Clostridium difficile infection (CDI). Methods: This was a retrospective, quasi-experimental study using interrupted time series (ITS) over 12 months before and after the intervention. The setting was adult medical and surgical wards in University Hospital Lewisham, an acute general hospital in London. The intervention was introduced in April 2006. Revised guidelines avoided broad-spectrum antibiotics, e.g. fluoroquinolones, cephalosporins, clindamycin, amoxicillin and co-amoxiclav, as they were considered to be 'high risk' for CDI. Instead, 'low risk' antibiotics such as penicillin, clarithromycin, doxycycline, gentamicin, vancomycin, trimethoprim and nitrofurantoin were recommended. Changes in antibiotic usage and incidence of CDI before and after the intervention were compared using segmented regression analysis. The negative binomial model was used to analyse the time series to estimate the CDI incidence rate ratio (IRR) following the intervention. Results: The intervention was associated with a significant reduction in the use of fluoroquinolones by 105.33 defined daily doses (DDDs)/1000 occupied bed-days (OBDs) per month [95% confidence interval (CI) 34.18-176.48, P<0.001] and cephalosporins by 45.93 DDDs/1000 OBDs/month (95% CI 24.11-67.74, P<0.0001). There was no significant change in total antibiotic, clindamycin, amoxicillin or co-amoxiclav use. There was a significant decrease in CDI following the intervention [IRR 0.34 (0.20-0.58), P<0.0001]. Conclusions: Revised antibiotic guidelines and enhanced stewardship was associated with a significant stepwise reduction in the use of cephalosporins and fluoroquinolones and a significant decrease in the incidence of CDI. © The Author 2011. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy. All rights reserved.